2017
DOI: 10.2147/cmar.s129059
|View full text |Cite
|
Sign up to set email alerts
|

APF530 versus ondansetron, each in a guideline-recommended three-drug regimen, for the prevention of chemotherapy-induced nausea and vomiting due to anthracycline plus cyclophosphamide–based highly emetogenic chemotherapy regimens: a post hoc subgroup analysis of the Phase III randomized MAGIC trial

Abstract: BackgroundAPF530, a novel extended-release granisetron injection, was superior to ondansetron in a guideline-recommended three-drug regimen in preventing delayed-phase chemotherapy-induced nausea and vomiting (CINV) among patients receiving highly emetogenic chemotherapy (HEC) in the double-blind Phase III Modified Absorption of Granisetron In the prevention of CINV (MAGIC) trial.Patients and methodsThis MAGIC post hoc analysis evaluated CINV prevention efficacy and safety of APF530 versus ondansetron, each wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(34 reference statements)
2
3
0
Order By: Relevance
“…However, under such a condition, the control of CINV was insufficient: 48% for complete response, 32% for complete control, 32% for the rate of no nausea, and 48% for the rate of no significant nausea during overall period, although vomiting was well controlled (78% for no vomiting during overall period). The rates of control of CINV during overall period observed in the present study were generally consistent with those reported by other investigators in breast cancer patients receiving AC chemotherapy: the complete response rate was similar to the data (47%) by Yeo et al (12), that (50%) by Hesketh et al (14) and within a range (36-82%) reported by others (8,11,13,15,22,23). The rates of no nausea and no vomiting were also within the range reported by other investigators [31-49% for nausea (8)(9)(10)(11)(12); 55-92% for vomiting (9-12, 13-16)].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, under such a condition, the control of CINV was insufficient: 48% for complete response, 32% for complete control, 32% for the rate of no nausea, and 48% for the rate of no significant nausea during overall period, although vomiting was well controlled (78% for no vomiting during overall period). The rates of control of CINV during overall period observed in the present study were generally consistent with those reported by other investigators in breast cancer patients receiving AC chemotherapy: the complete response rate was similar to the data (47%) by Yeo et al (12), that (50%) by Hesketh et al (14) and within a range (36-82%) reported by others (8,11,13,15,22,23). The rates of no nausea and no vomiting were also within the range reported by other investigators [31-49% for nausea (8)(9)(10)(11)(12); 55-92% for vomiting (9-12, 13-16)].…”
Section: Discussionsupporting
confidence: 93%
“…However, the control of CINV associated with AC chemotherapy is not necessarily sufficient, even when the guideline-consistent three-drug antiemetic premedication is implemented. Particularly, the rate of no nausea is too low (31-49%) (8)(9)(10)(11)(12) compared to the rate of no vomiting (55-92%) (9)(10)(11)(12)(13)(14)(15)(16). We also previously reported that AC chemotherapy for breast cancer is most emetogenic among various chemotherapy regimens that were carried out in the outpatient setting, in which the odds ratio (OR) for incidence of CINV is 4.955 [95% confidence interval (CI)=1.863-13.18; p=0.001] (17).…”
mentioning
confidence: 99%
“… 54 In a post hoc subgroup analysis of the 589 patients (65%) receiving AC-based HEC, at least 98% of whom were women, delayed-phase CR rates showed a trend favoring the GERSC arm (64%) over the ondansetron arm (56%). 95 A similar trend was found in the subgroup of 252 patients scheduled to receive cisplatin, where delayed-phase CR rates were numerically higher in the GERSC arm (65%) than in the ondansetron arm (55%). 96 These subgroup findings were consistent with the overall population, although the analyses were not powered to show a significant difference between groups.…”
Section: Efficacy Of Combination Therapies For Cinvsupporting
confidence: 63%
“…Although there are inherent challenges in comparing results across trials, it is encouraging that the complete response rates in this (and the prior oral NEPA) study are higher than those seen for other NK 1 triplet regimens in the AC setting (e.g., overall complete response rates in phase III trials: oral aprepitant 51% , fosaprepitant (51%–56%) , and oral rolapitant 63% ). It is noteworthy that these NK 1 RAs were combined with first‐generation 5‐HT 3 RAs ondansetron (aprepitant/fosaprepitant trials) and granisetron (rolapitant trial).…”
Section: Discussionmentioning
confidence: 74%